Music Culture in the Omaha Tribe of North America and the Saami of Northern Scandinavia: An Analysis of the Similarities and Possible Cultural Connections between Vuolle and Be-thae wa-an - Wirtanen, Trevor (2014)
This paper originally included a CD with 4 audio tracks on it. The CD was labeled "1. Vuolle 1 / 2. Vuolle 2 performed by Anders Gustav Fjällman / 3. Be-thae Wa-an 1 / 4. Be-thae Wa-an 2 performed by George Miller." Due to copyright restrictions the audio tracks could not be uploaded. Within both the Saami of northern Scandinavian and the Native American tribe known as the Omaha, there exists a rich and complex musical culture. This essay analyzes the intricacies and aural similarities of the aforementioned cultures and strives to determine the causation of their distinct musical parallels specifically between the be-thae wa-an of the Omaha and the vuolle of the southern Saami.